Proton pump inhibitors and risk of dementia - Wijarnpreecha K. (2017)
© Annals of Translational Medicine. All rights reserved. Background: Proton pump inhibitors (PPIs) are one of the most commonly prescribed medications. Recent studies have raised a concern over increased risk of dementia among PPIs users but the results of those studies were inconsistent. We conducted this systematic review and meta-analysis to summarize all available data. Methods: A literature search was performed in MEDLINE and EMBASE database from inception to April 2016. Observational studies that reported risk of dementia among PPIs users compared with non-users were included. Point estimates were extracted from individual studies and pooled risk ratios (RR) with 95% confidence intervals (CI) were calculated using a random-effect, generic inverse variance method. Results: Four studies were included in the analysis. Pooled RR of dementia among PPIs users compared with non-users was 1.08 (95% CI, 0.82-1.43). Sensitivity analysis including only cohort studies demonstrated a higher risk with pooled RR of 1.44 (95% CI, 1.36-1.52). Conclusions: Our study demonstrated an increased risk of dementia among PPIs users. Whether this association is causal requires further investigations.